2002
DOI: 10.1139/p01-150
|View full text |Cite
|
Sign up to set email alerts
|

Studies for the Odin sub-millimetre radiometer. II. Retrieval methodology

Abstract: This paper presents the first algorithm developed to retrieve atmospheric vertical profiles of trace gases from calibrated spectra measured by the sub-millimetre radiometer (SMR) onboard the Odin satellite. An estimation of atmospheric profiles is obtained by means of an inversion of the spectra using the Optimal Estimation Method. Great attention is paid to the study of the simultaneous retrieval of several species and nonlinearity effects. The measurement response is defined to give the altitude domain of a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 3 publications
1
34
0
Order By: Relevance
“…The time period 2002 shows up to 50 % smaller mixing ratios compared to OSO. One reason for the observed difference between the OSO and MIPAS (12 + 13) mesospheric CO datasets can be due to baseline features seen in the OSO spectra before February 2004.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…The time period 2002 shows up to 50 % smaller mixing ratios compared to OSO. One reason for the observed difference between the OSO and MIPAS (12 + 13) mesospheric CO datasets can be due to baseline features seen in the OSO spectra before February 2004.…”
Section: Discussionmentioning
confidence: 94%
“…A row in the AVK matrix can be regarded as a smoothing function (averaging kernel) describing the vertical resolution of the retrievals. The area of this smoothing function is called the measurement response and gives a rough indication of the contribution of the measurement to the retrieved value (Baron et al, 2002).…”
Section: Terminologymentioning
confidence: 99%
“…The value of this sum is generally referred to as the measurement response (Baron et al, 2002;Rodgers, 2004) and is shown by the black line in Fig. 3c.…”
Section: Results Of the Retrievalsmentioning
confidence: 99%
“…This figure also shows measurement response m and averaging kernel A. Details on m are explained by Baron et al (2002), and we simplified them as…”
Section: Methods Of Error Calculationmentioning
confidence: 99%